2017
DOI: 10.1159/000475438
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Mcl-1 through GSK-3β Activation Regulates Apoptosis Induced by Bufalin in Non-Small Cell Lung Cancer H1975 Cells

Abstract: Background/Aims: Mcl-1, an anti-apoptotic Bcl-2 family member, is often overexpressed in non-small cell lung cancer (NSCLC). Bufalin has been reported to induce apoptosis in various tumor cells. However, there is no report showing that bufalin could downregulate Mcl-1 expression in NSCLC. Methods: Cell proliferation was analyzed by cell counting kit-8 (CCK-8) assay in H1975 cells. Cell apoptosis was detected by flow cytometry. Mcl-1 mRNA was detected by RT-PCR. The expression of apoptosis-associated proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers. A large number of studies have indicated that Bufalin has the inhibitory effect on many kinds of malignant tumors, such as liver cancer [25], colorectal cancer [26], bladder cancer [27], gallbladder cancer [28], pancreatic cancer [29] and gastric cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers. A large number of studies have indicated that Bufalin has the inhibitory effect on many kinds of malignant tumors, such as liver cancer [25], colorectal cancer [26], bladder cancer [27], gallbladder cancer [28], pancreatic cancer [29] and gastric cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…The release of cyto-C from mitochondria into the cytosol leads to irreversible apoptotic signaling cascade [31]. The mitochondrial membrane permeability is under strict control of Bcl-2 family and counter-acted by Bax [32]. Our previous study preliminarily demonstrated that the strong cell penetration of stable CSIO in A549 and H1299 inhibited cell proliferation and induced cell apoptosis via down-regulating anti-apoptotic Bcl-2 and up-regulating pro-apoptotic P53 and caspase-3 [12].…”
Section: Discussionmentioning
confidence: 99%
“…GSK3 β activation by CG is downstream of NKA since it is no more observed in cells underexpressing NKA-A1 pump. GSK3β activation by bufalin and other CG such as ouabain and resibufogenin has been recently shown in liver, lung, and colon cell lines 33 36 .…”
Section: Discussionmentioning
confidence: 98%